P138 Kinetics of intrathoracic pressure change following administration of cpap. (15th November 2017) - Apps, MCP; Walsted, E; Pavitt, M; Swanton, L; Lewis, A; Buttery, S; Garner, J; Hopkinson, N; Polkey, M; Hull, J
Abstract : Introduction: An understanding of the changes in intra-thoracic pressure in response to application of Continuous Positive Airway Pressure (CPAP) is important in the study of thoracic and ventilator mechanics and device tolerability. It is unclear how quickly intra-thoracic pressure, measured directly with balloon catheters, responds to a change in CPAP. The aim of this study was to evaluate the kinetics of pressure stabilisation in healthy subjects. Methods: Mouth pressure (Pmo) was measured directly at the facemask of a NIPPY3 CPAP system, oesophageal pressure (Poes) and gastric (Pga) pressures were measured with balloon catheters in healthy subjects (n=7), seated at rest, with 10 min spontaneous ventilation followed by 20 min at CPAP of 5 cm/H2 0, then 20 min at CPAP 10 cm/H2 0, then 10 min no CPAP. Results: Pmo was lower than the setting for CPAP on the NIPPY3 machine; for CPAP=5 cm/H2 0 mean Pmo=4.67 cm/H2 0, SD 0.29 cm/H2 0; for CPAP=10 cm/H2 0, mean Pmo=9.09 cm/H2 0, SD 0.3 cm/H2 0. Poes with 5 cm/H2 0 was higher than with no CPAP; 3.31 v 0.13 cm/H2 0, p<0.05; with 10 cm/H2 0, 5.16 v 3.31 cm/H2 0, p<0.05; with CPAP back to 0 cm/H2 0, 5.18 v 1.1 cm/H2 0, p<0.05. There was a wide variability of gastric pressures both with and without CPAP; no significant changes in Pga with CPAP. Stabilisation of Pmo and Poes pressures after CPAP settings were changed occurred within 2 min for change in CPAP from 0–5 cm/H2 0, 5–10 cm/H2 0, and 10–0 cm/H2 0 with Pmo maximum time to stabilise 80 s, Poes maximum time to stabilise 86 s. Pga stabilisation took longer; for CPAP setting change 0–5 cm/H2 0, time to stability for Pga was 111–470 s; for CPAP 5–10 cm/H2 0, 46–183 s; for CPAP setting change 10–0 cm/H2 0, 37–135 s. Conclusions: In healthy subjects the kinetics of thoracic pressure stabilisation, following application of CPAP, is highly variable. Gastric pressure takes longer to stabilise and varies more than Pmo and Poes. This may reflect variation in diaphragm tonicity, gastric contraction or abdominal wall tone. These variable time constraints need considering when evaluating CPAP intervention. Subject variability in gastric pressure may contribute to reduced tolerability in some individuals and requires further study.